Almodóvar’s Baroque Transitions in the Early Films (1980–1995) - Frederic Conrod (Humanities)
Spanish film director Pedro Almodóvar has been detected early on by film critics as a Baroque filmmaker, a qualification to which he has agreed in interviews. This promotion of his style is certainly questionable as the word ‘Baroque’ is often used outside of its artistic and historical contexts. It is undeniable, however, that there are many Baroque features in his tragicomedy. One of the key aspects that ties Almodóvar’s early films to Baroque art is their exaggerated and melodramatic storytelling. Like Baroque art, which often featured grandiose and emotionally charged narratives, Almodóvar’s films are filled with intense emotions, complex relationships, and larger-than-life characters. This exaggerated portrayal of human emotions and experiences is a hallmark of Baroque aesthetics, which sought to evoke strong emotional responses from the audience. This paper seeks to focus exclusively on the rise of the director’s style in the last two decades of the 20th century that corresponds to Spain’s problematic and somewhat tragic transition from dictatorship to democracy and explore the ‘Baroque transitions’ that led Almodóvar to national, European and international recognition prior to the obtention of the Academy Awards he received for “All about my mother” in 2000. After defining the Baroqueness of his early filmography, this article will take a closer look at the ricochet trajectory he designed for actors such as Carmen Maura, Victoria Abril, and Antonio Banderas, who will all act in several corresponding roles and embody characters in transition, before becoming emblematic for the public. In the tradition of the Spanish Baroque, Almodóvar will develop his tragic outlook on his ever-changing culture around these iconic actors who will, in turn, unfold the complexity of the transition years for Spanish women and men.